2015
DOI: 10.1080/02664763.2015.1017719
|View full text |Cite
|
Sign up to set email alerts
|

Co-authorship networks and scientific performance: an empirical analysis using the generalized extreme value distribution

Abstract: This paper aims to explore the effects of collaborative behaviour on scholar scientific performance. Individual network measures related to scholar centrality as well as attitude to collaborate with others are derived from co-authorship networks in a given scientific community (i.e. Italian academic statisticians). Co-authorship information have been collected from three data sources of national-based, discipline-based, and international-based high-impact publications. Both network and individual covariates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…On the other hand, a low betweenness centralized network is a closed network. One study of the research networks of Italian statisticians found that closed networks had a negative effect on individual scientists' performance (De Stefano and Zaccarin 2015). Research has also found out that central authors have a high level of control, receive more citations (Ortega 2014), and a high g-index (Abbasi, Chung, and Hossain 2012;Abbasi, Wigand and Hossain 2014) in sparse ego networks.…”
Section: The Effect Of Scientists' Betweenness Centrality Of Ego-cent...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a low betweenness centralized network is a closed network. One study of the research networks of Italian statisticians found that closed networks had a negative effect on individual scientists' performance (De Stefano and Zaccarin 2015). Research has also found out that central authors have a high level of control, receive more citations (Ortega 2014), and a high g-index (Abbasi, Chung, and Hossain 2012;Abbasi, Wigand and Hossain 2014) in sparse ego networks.…”
Section: The Effect Of Scientists' Betweenness Centrality Of Ego-cent...mentioning
confidence: 99%
“…First, little research has examined scientists' productivity and impact at the same time (with the exception of Eisend and Schmidt's 2014 study) despite the fact that scientists' performance includes productivity (the number of papers), impact (citation counts, Oguz, Kingsley and John 2014), and the order of authors' names on publications (Abramo, Cicero and D'Angelo 2013). Second, although researchers have analyzed co-authorship networks to describe knowledge flow among co-authors, until recently, most studies have ignored the effect of the characteristics of ego-centered co-authorship networks on scientist performance (Letina 2016;De Stefano and Zaccarin 2015). An ego-centered co-authorship network is a network of a specific scientist (ego) and his/her co-authors (actors) (Letina 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades social network analysis (SNA) has become a widespread methodological approach to study scientific collaboration. As stated in several studies [5,8], scientific collaboration is a crucial factor to enhance publication productivity and research quality. The role of scientific collaboration allowing a fertile ground for the development of new ideas is also recognized in research funding European programmes as well as national projects.…”
Section: Introductionmentioning
confidence: 99%
“…This first step will be to differentiate networking from scientific activity (Cainelli et al, 2012(Cainelli et al, , 2015Schubert, 2012) by highlighting anomalies in a CV that potentially arise from the questionable practice of unjustified cross-citations by authors. Indeed, networking might be beneficial if it increases the cultural exchanges between organizations (De Stefano & Zacccarin, 2016), but it is detrimental if it affects researchers' attitudes towards scientific interests and publishing (McCarty & Jawitz, 2013). In other words, each organization should be in a position to transparently evaluate the networking activity of each researcher.…”
Section: Introductionmentioning
confidence: 99%